“From psychology in Africa to African psychology”: Going nowhere slowly - Makhubela, Malose (PINS-Psychology in Society, 2016)
This provocation reimagines the dominant indigenisation discourse of psychology in South Africa, which conceives the process of “decolonizing” as equivalent to “Africanizing”. I argue that some African psychologists’ indefatigable insistence on narrow localism and ethno-theorising, is a cowardly defeatism and an accessory to domination. The in toto refusals of Western psychology, are themselves ahistorical and totally ignorant of the historicity and historical anteriority of Africa in science. Western knowledge is neither monolithic, nor the sole property and prerogative of the West. Africa has significantly contributed to its creation and should admissibly make foundational claims on it. I gesture at a different decolonial ethics, grounded on the Dusselian transmodernity, pluriversalism and ethical universalism, to negotiate the incongruous obscure particularism of some African psychologists, and also disabuse modernist psychology of its false universalisms. The paper reads ultra-essentialist responses to modernism as still being intrinsically Eurocentric, in that they have rather ironically continued to reinforce the process of “Othering” and negating through their fixation with identity politics and cultural reductionism.